Analisis Stres Finansial Pada Gender - Peter Garlans Sina; Lidya Theresye Raturomon (Universitas Negeri Yogyakarta, 2012)
The aim of this research is to determine the tendency of financial stress as well as the differences between gender categories. The sampling method used is the census with a chi square technique. After the analysis, the results show that both of the hypothesis are accepted, which means that there is a tendency to experience a financial stress and the women tend to experience higher financial stress compared with men. This is due to an mistake in the management of personal finance. Key word : personal finance, financial stress, Gender